Adverbial of degree and its connotation - A comparative study of Arabic and Chinese - Xianan, Li (Journal of Humanities & Social Sciences, 2021)
This study aimed to reveal the difference between adverbial of degree in Arabic and adverbial of degree and range in Chinese from meaning and form, and focused mainly on analyzing the differences of adverbial of degree both in Arabic and Chinese, and indicated the problems that should be paid attention to in the process of Chinese translation. The analytical, descriptive and inductive approaches were used in the study, as the analysis and clarification were carried out through four chapters under the supervision of the aforementioned approaches. And the study reached a set of results, the most important of which are: the Arabic adverbial of degree is equal to the Chinese adverbial of degree in terms of meaning; there is a clear difference between them in terms of form; the practical application during Chinese translation is not only influenced by the expressive habit, but also by other elements such as context, artistic beauty, etc. therefore the recommendations and proposals given in the study cannot be considered a viable solution to all problems. Rather, they are considered as a beacon of enlightenment for specialists or those loving comparative study between these two great languages.